Highly sulfonated poly(ether ether ketone) grafted on graphene oxide as nanohybrid proton exchange membrane applied in fuel cells. (1st September 2018) - Gao, Shuitao; Xu, Hulin; Fang, Zhou; Ouadah, Amina; Chen, Huan; Chen, Xin; Shi, Lubin; Ma, Bing; Jing, Chaojun; Zhu, Changjin
Abstract: Highly sulfonated poly(ether ether ketone) (PEEK) polymer is hydrogenated and then readily grafted on GO to provide nanohybrid material GO-g-SPEEK. The material shows good enough properties for the preparation of proton exchange membranes. First, the GO-g-SPEEK membrane has much more water uptake but less water swelling compared with Nafion ®, and an excellent proton conductivity of 0.219 Scm −1 at 90 °C. Then, it demonstrates a peak power density of 112 mWcm −2 when utilized in a H2 /air fuel cell at circumstance temperature. Further, blending of the materials with Nafion leads to composite membranes of GO-g-SPEEK/Nafion, which has a close proton conductivity to that of GO-g-SPEEK but far higher cell performances. Of the composite membranes, GO-g-SPEEK/Nafion-33 reveals cell performance of 182 mWcm −2 at 25 °C and 213 mWcm −2 at 60 °C. These results indicate that Nafion might serve only as an enhancer of compatibility between membrane and Nafion-supported catalyst phase in the membrane electrode assembly, and therefore suggest that the GO-g-SPEEK may be a promising membrane material for the application in proton exchange membrane fuel cells.